Plasma Levels of Brain-Derived Neurotrophic Factor and S100B in Relation to Antidepressant Response to Ketamine - Jiang, Haitang; Veldman, Emma R.; Tiger, Mikael; Ekman, Carl-Johan; Lundberg, Johan; Svenningsson, Per (Frontiers in Neuroscience, 2021)
Background: Evidence demonstrates that the neurotrophins brain-derived neurotrophic factor (BDNF) and S100 calcium-binding protein B (S100B) have a pivotal role in the pathogenesis of Major Depressive Disorder (MDD) and they are proposed as predictors of antidepressant response. Ketamine produces rapid antidepressant effects in MDD and pre-clinical studies suggest the necessity of increased BDNF levels for the antidepressant action of ketamine. However, studies observing the change of blood BDNF levels after ketamine intervention are inconsistent and studies about the role of plasma S100B in ketamine administration in MDD patients are lacking. Method: We evaluated mature BDNF (mBDNF), S100B levels in plasma and their associations with depression severity in 30 Selective Serotonin Reuptake Inhibitor-resistant (SSRI) MDD patients enrolled in a randomized controlled trial of ketamine compared (n=20) to a placebo (n=10) control (saline). Severity of depression was assessed using the Montgomery–Åsberg Depression Rating Scale (MADRS). Results: Plasma mBDNF and S100B were not significantly changed after 1-2 days of single ketamine compared to placebo. Plasma mBDNF and S100B levels did not significantly differ in responders compared to non-responders of ketamine treatment. The change of plasma mBDNF levels was positively correlated with the improvement of MADRS score after 1-2 weeks of open-label ketamine treatment (rho = 0.495, p = 0.031), though this change did not survive correction for multiple comparisons. Conclusions: These findings do not support the hypothesis that ketamine treatment increases BDNF plasma levels in MDD patients. No effect of ketamine treatment on S100B plasma levels was seen.